Interplay between low threshold voltage-gated K+ channels and synaptic inhibition in neurons of the chicken nucleus laminaris along its frequency axis - Hamlet, William R.; Liu, Yu-Wei; Tang, Zheng-Quan; Lu, Yong (Frontiers in Neural Circuits, 2014)
Central auditory neurons that localize sound in horizontal space have specialized intrinsic and synaptic cellular mechanisms to tightly control the threshold and timing for action potential generation. However, the critical interplay between intrinsic voltage-gated conductances and extrinsic synaptic conductances in determining neuronal output are not well understood. In chicken, neurons in the nucleus laminaris (NL) encode sound location using interaural time difference (ITD) as a cue. Along the tonotopic axis of NL, there exist robust differences among low, middle, and high frequency (LF, MF, and HF, respectively) neurons in a variety of neuronal properties such as low threshold voltage-gated K+ (LTK) channels and depolarizing inhibition. This establishes NL as an ideal model to examine the interactions between LTK currents and synaptic inhibition across the tonotopic axis. Using whole-cell patch clamp recordings prepared from chicken embryos (E17-E18), we found that LTK currents were larger in MF and HF neurons than in LF neurons. Kinetic analysis revealed that LTK currents in MF neurons activated at lower voltages than in LF and HF neurons, whereas the inactivation of the currents was similar across the tonotopic axis. Surprisingly, blockade of LTK currents using dendrotoxin-I (DTX) tended to broaden the duration and increase the amplitude of the depolarizing inhibitory postsynaptic potentials (IPSPs) in NL neurons without dependence on coding frequency regions. Analyses of the effects of DTX on inhibitory postsynaptic currents led us to interpret this unexpected observation as a result of primarily postsynaptic effects of LTK currents on MF and HF neurons, and combined presynaptic and postsynaptic effects in LF neurons. Furthermore, DTX transferred subthreshold IPSPs to spikes. Taken together, the results suggest a critical role for LTK currents in regulating inhibitory synaptic strength in ITD-coding neurons at various frequencies.